Relationships between Outdoor Walking Levels and Neighbourhood Built-Environment Attributes: The Case of Older Adults in Birmingham, UK - Zandieh, R. (CRC Press, 2020)
The research we describe in this chapter had two aims: (1) to illustrate the capacity of GIS for generating objective measures of macro built-environment attributes; and (2) to use GIS-measured macro built-environment attributes, together with perceived micro built-environment attributes, to examine correlations among and between neighbourhood built-environment attributes in order to better understand how to increase positive (or to decrease negative) influences of neighbourhood built-environment attributes on outdoor walking levels.